Pengelolaan Zakat Produktif untuk Meningkat Usaha Kecil dan Menengah - Pauzi Muhammad (NALAR FIQH: Jurnal Hukum Islam, 2014)
In the kontext of productive charity, the intended meaning is the first meaning in growth. In economic terms in known as growth (growth capital) or wealth (wealth growth). How did it happen? One of the main functions of the zakat is one way to prevent hoarding property which may result in death or wealth does not grow. So it is recommended to place the property in the form of productive assets, such as funds placed in banks or gevernment-controlled institutions. The small dan medium businesses charity distribution sector include: (1) agriculture, livestock, forestry and fisheries; (2) trade, hotels and restaurants; (3) the processing industry; (4) services; and (5) transport and communications. While the economic sectors that have the smallest proportion of business units in a row is a sector: (1) Electricity, gas and water supply; (2) finance, leasing and business service; (3) building; and (4) mining and quarring. Indonesian muslims who are the majority, have great potential in helping to alleviate poverty through charity programs. However, this potential has not managed optimally, there are many muslims who angaged in small and medium business has not helped in developing venture capital. With the distribution of charity for small and medium businesses cas increase revenue for the community engaged in the small and medium enterprises, so as in improve the welfare of the people.